Determination of a Local Hybrid Geoid as a Height Reference System for 3D Cadastre - Margaretha Elya Lim Putraningtyas; Leni Sophia Heliani; Nurrohmat Widjajanti; Trias Aditya (Faculty of Geography, Universitas Gadjah Mada, 2021)
Use and development of vertical building(s) on land parcel(s) have been a common progress to many urban landscapes around the world. 3D cadastre has been a research area that involves legal, technical and institutional assessments to the use and development of vertical buildings. Initial Land Registration of 3D cadastre objects require a representative geometry to determine the legal boundaries of 3D objects. For that purpose, a height reference that is used to define 3D geometries of registered 3D cadastre objects is important. This study focuses in determining a height reference system by developing a local hybrid geoid for the representation of 3D cadastre. The local hybrid geoid was developed by fitting the gravimetric to the geometric geoid. Four strategies were utilized, based on the combination of GGM’s SGG-UGM-1 and GO_CONS_GCF_2_SPW_R5, Remove-Compute-Restore method and control point distribution for geoid fitting. Based on comparison with geometric geoid at six independent control points, the local hybrid geoid from strategy 3 produces mean difference of 0.354 m, accuracy of 0.137 m and increased level of closeness of 86%, which is further applied as an alternative reference surface in 3D cadastre.